The Influence of Trust and Perceived Ease of Use on the Adoption of Digital Wallets as an Alternative Payment among Gen Z Mediated by User Satisfaction - Violettasari, Yolanda; Kurniawan, M. Yusuf; Arumsari, Yuni Kusuma (Fakultas Ekonomi Universitas Kadiri, 2025)
The research aims to analyse the influence of trust and perceived convenience on the adoption of digital wallets as payment alternatives among Gen Z, with user satisfaction as a mediating variable. In the era of rapidly growing digitalisation, digital wallets are the main choice for Gen Z in making transactions. This research uses a quantitative approach, with respondents from Gen Z. The results of the analysis using the Partial Least Square (PLS) method show that trust and perceived convenience have a positive and significant effect on digital wallet adoption. User satisfaction is proven to mediate the relationship between trust and perceived convenience on digital adoption. This research provides insight for digital wallet service providers in designing strategies to increase user trust and satisfaction.